Strategi Pemasaran Kredit Kepemilikan Rumah (KPR) Pada Bank BTN Kantor Cabang Cilegon Di Tinjau Dari Analisis SWOT - Dicky Firdaus; Anas Hidayat (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
BTN Cilegon Branch Office is a bank that provides mortgage products that are in demand by the public, especially those who don't have a place to live. However, as time goes by, many other banks provide KPR products, therefore the BTN Cilegon Branch Office is required to prepare more effective marketing strategies. The problem raised by the author in the context of this research is regarding how the marketing strategy for KPR BTN products is viewed from a SWOT analysis. The implementation of this research was at PT. Bank Tabungan Negara (BTN) Cilegon Branch Office and utilizes qualitative research methods, namely by the author describing problems based on various existing data and then analyzing them to conclude. The results of this research are that the marketing of KPR products by Bank BTN Cilegon Branch Office uses an analysis strategy that combines two external and internal factors into the SWOT Matrix: SO Strategy, in the form of establishing communication with developers and potential customers. ST's strategy, namely finding the right and good marketing to promote KPR Sejahtera products compared to other bank marketing. WO's strategy, namely promoting to a wide audience by using its advantages as the largest mortgage disbursing bank in mortgage financing. WT's strategy is to provide good understanding to potential customers and provide marketing to market mortgage products more effectively.